Análisis de la aplicación profunda de briquetas de urea en el suelo como fuente de lenta liberación de nitrógeno en la producción de arroz - Calle, Olga (2010)
Rice cultivation is a major claimant of nitrogen fertilizers, as is considered the nutrient that most directly impact on production, it increases the percentage of filled spikelets, increases leaf area and also contributes to increased grain quality. To meet these nutritional needs the most purchased product is urea, but it produces a waste because of its method of implementation, caused by the volatilization of ammonia resulting from hydrolysis of urea in contact with water. That's why Asian countries, major rice producers, have successfully tested the use of deep application of urea briquettes. This technology prevents the volatilization of ammonia to the atmosphere since the hydrolysis of urea occurs in the anaerobic zone of the soil and not in the aerobic zone as in the case of the broadcast application. The study in CENAE was intended to check the technology used in Asia for which were made of soil and foliar analysis for each repetition during the periods of greatest demand for N by the plant